Effects of additional scapular movements on the scapular muscle activity during arm raising - Yu, Ilyoung; Kang, Minhyeok (International Journal of Sports Medicine, 2025)
The effects of the two popular strategies, scapular adduction and depression and scapular posterior tilt, on the muscle activity of trapezius and serratus anterior muscles have not been compared. This study demonstrates the effects of additional scapular adduction and depression and scapular posterior tilt movements on the activation of trapezius and serratus anterior muscles and scapular kinematics during arm raising. Eighteen asymptomatic men performed arm raising tasks with and without additional scapular movements, including scapular adduction and depression and scapular posterior tilt. During all tasks, the muscle activity of the upper/middle/lower trapezius and serratus anterior muscles was measured using surface electromyography; scapular upward rotation and posterior tilt angles were measured using a smartphone application. Lower trapezius muscle activity significantly increased during arm raising with scapular adduction and depression (p=0.001) or scapular posterior tilt compared to preferred arm raising (p<0.001). However, arm raising with the scapular posterior tilt showed significantly greater serratus anterior muscle activity (p=0.002) and scapular posterior tilt angle (p=0.001) together with lesser upper trapezius muscle activity (p=0.027) compared with those of scapular adduction and depression. Scapular posterior tilt may be effective for increasing the lower trapezius and serratus anterior muscle activity while reducing the upper trapezius muscle activity.
Keywords: biomechanical phenomena; electromyography; scapula; superficial back muscles